Homotopy perturbation method with modified Riemann –Liouville derivative for solving fractional- time partial differential equations - Majeed, Abeer (University of Thi-Qar Journal of Science, 2012)
The aim of this paper is to present an efficient and reliable treatment of the Homotopy perturbation method (HPM) and the modified Riemann –Liouville derivative for partial differential equations with fractional time derivative. The fractional derivative is described in the Jumarie sense. The results reveal that the proposed method is very effective and simple and leads to accurate, approximately convergent solutions to fractional partial differential equations.